Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/milmed/usy277
|View full text |Cite
|
Sign up to set email alerts
|

Modified Battlefield Acupuncture Does Not Reduce Pain or Improve Quality of Life in Patients with Lower Extremity Surgery

Abstract: Introduction This study seeks to determine if modified Battlefield Acupuncture is more effective at relieving acute extremity pain, reducing medication use, and improving quality of life than placebo acupuncture or standard care after lower extremity surgery. Methods We conducted a multi-site 3-arm randomized, double-blind controlled trial of standard care alone versus standard care + placebo auricular acupuncture with semi-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 10 publications
1
30
1
Order By: Relevance
“…As noted in other studies, opioid, NSAID, and acetaminophen use was similar between the groups (P > 0.05). 11,13,33 In contrast to Usichenko, et al's 2007 research on auricular acupuncture after ambulatory knee surgery 11 that showed significant reductions in ibuprofen use at 24 hours (P < 0.05), this study noted similar NSAID (ibuprofen or naproxen sodium) uses between the groups. Larger RCTs to evaluate auricular and BFA's (protocol and modified protocols) effect on musculoskeletal pain did not show significant differences in opioid use.…”
Section: Collinsworth and Gosscontrasting
confidence: 90%
See 1 more Smart Citation
“…As noted in other studies, opioid, NSAID, and acetaminophen use was similar between the groups (P > 0.05). 11,13,33 In contrast to Usichenko, et al's 2007 research on auricular acupuncture after ambulatory knee surgery 11 that showed significant reductions in ibuprofen use at 24 hours (P < 0.05), this study noted similar NSAID (ibuprofen or naproxen sodium) uses between the groups. Larger RCTs to evaluate auricular and BFA's (protocol and modified protocols) effect on musculoskeletal pain did not show significant differences in opioid use.…”
Section: Collinsworth and Gosscontrasting
confidence: 90%
“…31,32 Prior research investigating BFA's effect on musculoskeletal pain has produced positive results with clinically meaningful pain reduction without statistical significance. 11,33,34 The majority of randomized controlled trials (RCTs) performed using BFA and auricular acupuncture have been deemed ''less than rigorous'' due to small sample sizes, lack of blinding (therapists and subjects), and lack of sham acupuncture. 35 Prior research has shown the MCID for the VAS of pain ranging from 13 to 19 mm.…”
Section: Collinsworth and Gossmentioning
confidence: 99%
“…We elected to forgo a sham treatment group due to lack of feasibility in maintaining a realistic sham treatment at our institution. The most recent study of BFA that utilized a sham intervention applied the treatment while the patient was still under anesthesia (Crawford 2019). BFA represents a low-risk and low-cost alternative method of pain control when compared to opioid medications, making the potential for a placebo contribution to the response to treatment more acceptable [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, following lower extremity surgery patients reported similar pain, opiod use, and quality of life with BFA plus standard care compared with standard of care alone or placebo treatments [26]. Most recently, BFA supplemented with standard care resulted in great pain reduction throughout the rst week after shoulder surgery compared to standard care alone in a small cohort of U.S. Military Academy Cadets [27].…”
Section: Introductionmentioning
confidence: 97%
“…In a study of 30 patients presenting to an emergency department with low back pain, the addition of BFA to standard care resulted in signi cantly reduced pain when compared with standard care alone [19]. Conversely, in a study of 233 patients following lower extremity surgery, BFA applied within 30 minutes of arrival to the post-anesthesia care unit did not result in signi cantly reduced pain, reduced opioid use, or improved quality of life when compared with standard of care or placebo treatments [20]. Most recently, in a study of 40 U.S. Military Academy Cadets who underwent shoulder surgery, those receiving BFA 24-hours after surgery demonstrated signi cantly reduced worst and average pain from baseline to 1-week post-surgery, with con dence intervals that suggest promising, but not conclusive results [21].…”
Section: Introductionmentioning
confidence: 97%